Neglect is a Spatial Failure of Alerting Mechanisms Required for Awareness: An ERP Study - Heikki Hämäläinen; Myoung Soo Kwon; Arja Lindell; Maarit Jalas; Jutta Torsti; Olli Tenovuo (Journal of Basic & Applied Sciences, 2014)
In the present study, we describe a group of right brain-damaged (RBD) patients with neglect or extinction, most of them affected in all three (visual, auditory, somatosensory) modalities studied. We applied event-related potential (ERP) analysis to reveal the neural mechanisms underlying hemispatial neglect. ERPs to stimuli of all three modalities were determined for the patients with neglect/extinction at (sub)acute phase, and 3 and 12 months post-stroke. Our results demonstrated that N1 deflections in ERPs, reflecting fronto-parietal alerting mechanisms, wereabsent or diminished/delayed in neglect, and the waves became normalized with recovery from neglect. In somatosensory ERPs, similar changes were evident also in P1 deflections preceding the N1, reflecting activation of the secondary somatosensory cortex (SII). We also demonstrated somatosensory ERPs of some of our patients who showed different responses elicited by low intensity electrical stimulation of the median nerve at the wrist depending on the location of the hands either in uncrossed anatomical position or crossed over the body midline to the other hemispace. Our results indicate that there are cases among patients with hemispatial neglect who do indeed show emergence or increment of responses to left-hand stimulation when the arm is crossed to the right hemispace. Therefore, we propose that the mechanism underlying hemispatial neglect is the disruption of the flow of (location related) sensory information to awareness at the level of multimodal alerting mechanisms.